The larvae of Epigomphus jannyae Belle, 1993 and E. tumefactus Calvert, 1903 (Insecta: Odonata: Gomphidae) - Novelo-Gutiérrez,Rodolfo; Ramírez,Alonso; Delgado,Débora (PeerJ, 2016)
The taxonomic knowledge about immature stages of the insect order Odonata (dragonflies and damselflies) is rather limited in tropical America. Here, the larvae of Epigomphus jannyae Belle, 1993 and E. tumefactus Calvert, 1903 are described, figured, and compared with other described congeners. E. jannyae larva is characterized by 3rd antennomere 1.6 times longer than its widest part; ligula very poorly developed, with ten short, truncate teeth on middle; apical lobe of labial palp rounded and smooth. Lateral margins on abdominal segments (S5–9) serrated, lateral spines on S6–9 small and divergent; male epiproct with a pair of dorsal tubercles at basal 0.66; tips of cerci and paraprocts strongly divergent. The larva of E. tumefactus is characterized by 3rd antennomere 2.3 times longer than its widest part, ligula with 6–7 truncate teeth, apical lobe of labial palp acute and finely serrate. Lateral margins of S6–9 serrate, lateral spines on S7–9; male epiproct with a pair of dorsal tubercles at basal 0.50. Differences with other species were found in 3rd antennomere, lateral spines of S7–9, and the caudal appendages. Epigomphus larvae inhabit small, shallow creeks (1st order streams) where they live in fine benthic sediments. When mature, the larva leaves the water in shady places, climbing small rocks at the water’s edge and metamorphosing horizontally on flat rocks. These new descriptions bring the total number of Epigomphus species with known larval stages to eight; only 28% of the species in this genus are known as larva.
Keywords: Odonata; Anisoptera; Gomphidae; Larval description; Taxonomy